Features of quality assessment in Germany - Shimpf, Karin; Pererva, P. G. (ФОП Панов А. М., 2023)
The German system of evaluating the quality of education is fundamentally different from most others. Many students who come to study from abroad cannot get used to the rules for calculating grades for a long time. German schools use a six-level methodology. Compared to other countries, the highest score is one.
Особливості оцінки якості в Німеччині
Keywords: education; higher school; quality assessment; education standards